The Effects of Booklet Media on the Knowledge of Prospective Brides and Grooms Regarding Physical and Psychological Preparation at the KUA of Sokaraja District - Kusumawardani, Alfia Putri; Linggardini, Kris (UM Purwokerto Press, 2025)
Prospective brides and grooms are two individuals planning to start a life together in marriage, aiming to form a harmonious and sustainable family. They need to prepare their reproductive health, both for the bride and groom, so that after marriage, they can have a good health status to produce a quality generation. This quantitative research used a Pre-Experiment approach with One Group Pre-Test and Post-Test design. The population in this study was 492 prospective brides and grooms, with a sample of 44 respondents. Data analysis was performed using the Wilcoxon Test. Wilcoxon test results p-value of 0.00>0.05. Hypothesis (Ha) is accepted which shows the results of the study that there is a significant influence of booklet media on the knowledge of prospective brides and grooms. Booklet media. Booklet media significantly affects prospective brides and grooms' knowledge regarding physical and psychological preparation at the KUA of Sokaraja District.